2002
DOI: 10.5483/bmbrep.2002.35.6.576
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Collagenase from the Mackerel, Scomber japonicus

Abstract: Collagenase from the internal organs of a mackerel was purified using acetone precipitation, ion-exchange chromatography on a DEAE-Sephadex A-50, gel filtration chromatography on a Sephadex G-100, ion-exchange chromatography on DEAE-Sephacel, and gel filtration chromatography on a Sephadex G-75 column. The molecular mass of the purified enzyme was estimated to be 14.8 kDa by gel filtration and SDS-PAGE. The purification and yield were 39.5-fold and 0.1% when compared to those in the starting-crude extract. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 22 publications
10
31
0
1
Order By: Relevance
“…The optimum temperature depends on the type of enzyme, the analyzed tissue and the source species, and has been reported for collagenolytic enzymes in the range of 30°C and 60°C PARK et al, 2002;DABOOR et al, 2012;WU et al, 2010a;HAYET et al, 2011;SUPHATHARAPRATEEP et al, 2011;BAEHAKI et al, 2012;LIMA et al, 2013). Similar results to the present study were described for winter flounder P. americanus (TERUEL and SIMPSON 1995), filefish species N. modestrus , tuna T.…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymesupporting
confidence: 81%
See 2 more Smart Citations
“…The optimum temperature depends on the type of enzyme, the analyzed tissue and the source species, and has been reported for collagenolytic enzymes in the range of 30°C and 60°C PARK et al, 2002;DABOOR et al, 2012;WU et al, 2010a;HAYET et al, 2011;SUPHATHARAPRATEEP et al, 2011;BAEHAKI et al, 2012;LIMA et al, 2013). Similar results to the present study were described for winter flounder P. americanus (TERUEL and SIMPSON 1995), filefish species N. modestrus , tuna T.…”
Section: Temperature and Ph Assay Of The Collagenolytic Enzymesupporting
confidence: 81%
“…Hydrolysis of type I collagen has been detected by using collagenolytic proteases produced by various aquatic organisms, such as for the species of fish described by: KRISTJÁMSSON et al (1995) for Atlantic cod (G. morhua); TERUEL and SIMPSON, (1995) for winter flounder (P. americanus); BYUN et al (2002) for tuna (T. thymus); PARK et al (2002) for mackerel (S. japonicus); KIM et al (2002) for filefish (N. modestrus); HERREIRO-HERNANDEZ et al (2002) for iced cod (G. morhua); HAYET et al (2011) for sardinelle (S. aurita);and ROY et al (1996) for greenshore crab (C. maenas). In our studies, the intestinal protease of smooth weakfish was able to cleave the collagen type I tested, as shown in Figure 3.…”
Section: Hydrolysis Of Collagen By the Collagenolytic Enzymementioning
confidence: 99%
See 1 more Smart Citation
“…Teruel and Simpson (1995) isolated a collagenolytic enzyme from the skeletal muscle of winter flounder with greatest activity at a pH of 7.5 while the most enzyme activity of collagenolytic serine proteases isolated from digestive tracts of various fish and aquatic invertebrates (including crabs, prawns, crayfish and cod) is within the pH range of 6.5-8.0 . Other studies found slightly higher pH values (7.0-8.0) to be optimal for collagenolytic activity in the digestive tissues of crabs, mackerel and file fish (Sivakumar, et al, 1999;Park et al, 2002). Extremes of pH are to be avoided.…”
Section: Factors Affecting Collagenase Activitymentioning
confidence: 99%
“…Thus, particular care should be taken when using this method on semipurified extracts, with particular emphasis placed on blank measurements (Lim et al, 1993). Despite this limitation, this assay remains a relatively simple method to perform and a number of studies have successfully used it with minor modifications of the incubation time and/or the amount of the substrate to determine collagenases isolated from a variety of sources (Rosen, 1957;Yoshida and Noda, 1965;Endo et al, 1987;Sivakumar et al, 1999;Yin et al, 2002;Park et al, 2002;Wu et al, 2010). …”
Section: Colorimetric Assaysmentioning
confidence: 99%